Come together: The importance of arts and cultural engagement within the Liverpool City Region throughout the COVID-19 lockdown periods - Chapple, Melissa; Anisimovich, Antonina; Worsley, Joanne; Watkins, Megan; Billington, Josie; Balabanova, Ekaterina (Frontiers in Psychology, 2023)
Arts and cultural engagement activities have long been found to support mental health and wellbeing within the general population. In particular, community arts and cultural involvement during the COVID-19 pandemic has been an invaluable source of mental health support for many individuals across the globe. The initial move to remote engagement following the first UK lockdown demonstrated the importance of hybrid provisions, with isolated and vulnerable individuals finding online provisions important for wellbeing. With restrictions on movement and service access in the UK having gradually eased from March 2021, it is now important to explore how individuals navigated the ability to engage with either remote or in-person provisions. The current study aimed to explore the impact of the COVID-19 pandemic on arts and cultural engagement during periods of restrictions and initial easings on movement within the Liverpool City Region. Findings presented in the current study provide further evidence of the value of arts and cultural activities in supporting mental health and wellbeing. Specifically, the current data emphasise the value of arts and cultural engagement throughout the COVID-19 pandemic and particularly during times of national restriction. Furthermore, the current study demonstrated that remote engagement provided important mental health support throughout the pandemic, but with limitations on feelings of social connectedness within online environments. Amidst continuing risks from the COVID-19 virus and feelings of uncertainty, this study highlights the importance of hybrid provisions.